Modelling Dividend Policy and Firms’ Value Relations in Nigeria - Ejem, Chukwu Agwu; Ogbonna, Udochukwu Godfrey (International Journal of Economics and Financial Issues, 2019)
This study investigated the controversy raging between dividend policy and firms’ value in Nigeria. This study made use of 24 quoted companies selected from 10 sectors of Nigerian economy from firm’s annual reports and accounts for the period of 2012-2017. The results of the descriptive statistics found that few numbers of companies are paying high dividends, while the rest companies are paying very low or no dividends. The correlation test revealed that leverage firms are likely to pay lower dividends in Nigeria. Also, found absence of multicollinearity among the variables. The researchers fitted the three conventional models of panel data analysis and found earnings exerting positive and significant influence on the firms’ value, whereas dividend per share insignificantly impacts firms’ value. Likelihood ratio and Hausman tests rejected the null hypothesis that unobserved variables have no significant relationship with observed variables. The two tests back fixed effect that unobserved variables are important explanatory variable for firm’s value. Therefore, the researchers are suggesting that firms improve on their operations by managing the resources of their firms effectively and efficiently in order to increase earnings. Keywords: Dividend policy, Firm’s value, Earnings, Dividend per share, fixed effects. JEL Classifications: G32, C58 DOI: https://doi.org/10.32479/ijefi.8849